2019
DOI: 10.1111/ctr.13616
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of survival on the waiting list for heart transplantation and of posttransplant nonadherence—Results of a prospective longitudinal study

Abstract: Background Only a few previous studies have focused on the interaction between pretransplant psychological variables, survival on the waiting list, and adherence to therapy after heart transplantation (HTx). Methods This work combined two studies: Study 1 monitored survival of patients on a HTx waiting list (n = 50) and study 2 examined barriers to adherence after HTx (subgroup of n = 20). All patients were evaluated immediately after listing for HTx (T0). Those in study 2 were also evaluated immediately after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 33 publications
(46 reference statements)
0
14
0
Order By: Relevance
“…Whereas the medical effects of COVID-19 are several, the social effects of the pandemic may lead to a number of additional challenges related to adherence behavior. Poor psychosocial functioning [11], lack of social support [12] and worse mental health [13] are known correlates to low adherence to immunosuppressants among adult heart transplant recipients. Additionally, immunosuppressants can be costly with the need for insurance coverage, and taking these medications as recommended requires a high level of health literacy to incorporate effectively in daily routine.…”
Section: Challenges Of Adherence To Immunosuppression Medicationsmentioning
confidence: 99%
“…Whereas the medical effects of COVID-19 are several, the social effects of the pandemic may lead to a number of additional challenges related to adherence behavior. Poor psychosocial functioning [11], lack of social support [12] and worse mental health [13] are known correlates to low adherence to immunosuppressants among adult heart transplant recipients. Additionally, immunosuppressants can be costly with the need for insurance coverage, and taking these medications as recommended requires a high level of health literacy to incorporate effectively in daily routine.…”
Section: Challenges Of Adherence To Immunosuppression Medicationsmentioning
confidence: 99%
“…Pre-transplant depression was not related to missing posttransplant clinical follow-up appointments, occurrence of graft rejection, or duration of survival, although it increased patients' risk for rehospitalization [13]. Vitinius et al [12] found a strong association between pre-transplant anxiety symptoms and post-transplant perceptions of medication adherence barriers, but the association was not statistically significant due to their very small sample size.…”
Section: Mental Health Historymentioning
confidence: 96%
“…There were also no reliable relationships to clinical outcomes including graft rejection, length of hospital stay after transplant, time to rehospitalization, total hospital days, or number of rehospitalizations [41,42]. Two studies found no effect on mortality [40,41]; the third study reported equivocal evidence, depending on the method used to calculate "high-risk" using the psychosocial rating tool score [12].…”
Section: The Psychosocial Evaluation Processmentioning
confidence: 98%
See 2 more Smart Citations